Application of sequencing batch biofilm reactor (SBBR) in dairy wastewater treatment - Ozturk, Arzu; Aygün, Ahmet; Nas, Bilgehan (Korean Institute Chemical Engineers, 2019)
Application of lab-scale sequencing batch (SBR) and sequencing batch biofilm reactors (SBBR) for treatment of dairy wastewater was investigated under organic loading of 1,130-1,560 gBOD(5)/m(3)d. The main characteristics of the dairy wastewater were: pH=4.9, chemical oxygen demand (COD)=16,264 mg/l; biological oxygen demand (BOD5)=10,536 mg/l, PO4-P=342 mg/l; total nitrogen (TN)=224 mg/l. SBBR was filled with the Kaldnes K1 biocarrier at 30% of the volume of empty reactor. The SBR and SBBR were operated in fixed 24 h cycles, each consisting of 30 min fill up, 22 h aeration, 1.5 h settle, 30 min decant, and idle with a hydraulic retention time (HRT) of 8 days. Operational parameters such as pH, dissolved oxygen (DO), mixed liquor suspended solid (MLSS), solids retention time (SRT) and sludge volume index (SVI) were monitored during the whole cycle. The effects of these parameters on the COD, nitrogen and phosphorus removal were discussed in this paper. As a result, adding biocarrier to the reactor had a positive effect on organic with COD removal of 63.5% for SBR and 81.8% for SBBR and nutrient removal with ammonium removal of 66.0% for SBR and 85.1% for SBBR in treatment of dairy wastewater.
Keywords: COD Removal; Dairy Wastewater; Biocarrier; Nutrient Removal; SBR; SBBR